Development and Analysis Report Information System Quality Web-Based Student Learning Outcomes at SMK Negeri 1 Banyumas - Zahro, Avidah Amalia (Jurnal Manajemen Informatika Medicom (JMI), 2024)
The purpose of this study was to develop an information system for reporting student learning outcomes at SMK Negeri 1 Banyumas, knowing the level of quality of the information system reporting student learning outcomes based on quality testing in accordance with ISO 25010 standards. The method used in this study was Research and Development (R&D). The development of this information system is carried out in 4 stages according to the waterfall method, namely the analysis stage, the design stage, the coding or implementation stage and the testing stage. The results of this study are 1) a web-based student learning outcome report information system developed with the Codeigniter 3.0 framework. and has the main features to import, manage, print, and display student report cards. 2) the test results show that the information system has met the ISO 25010 standard in aspects (1) functional suitability runs 100% and has a value of X=1; (2) performance efficiency can load pages in 3.2 seconds, PageSpeed ​​performance of 94% (grade A) and YSlow of 90% (grade A); (3) usability, the percentage value is 84.69%; (4) security, with the level of vulnerability to attacks at level 1 (low); (5) reliability, with 100% session, hits and pages results; (6) maintainability has a maintainability index value of 68.28; (7) portability ran successfully on 5 different desktop browsers tested without error. PageSpeed ​​performance of 94% (grade A) and YSlow of 90% (grade A); (3) usability, the percentage value is 84.69%; (4) security, with the level of vulnerability to attacks at level 1 (low); (5) reliability, with 100% session, hits and pages results; (6) maintainability has a maintainability index value of 68.28; (7) portability ran successfully on 5 different desktop browsers tested without error. PageSpeed ​​performance of 94% (grade A) and YSlow of 90% (grade A); (3) usability, the percentage value is 84.69%; (4) security, with the level of vulnerability to attacks at level 1 (low); (5) reliability, with 100% session, hits and pages results; (6) maintainability has a maintainability index value of 68.28; (7) portability ran successfully on 5 different desktop browsers tested without error.